In silico analysis of antibiotic resistance genes in Lactiplantibacillus plan‐ tarum subsp. plantarum Kita‐3 - Angelia Wattimury; Rachma Wikandari; Dian Anggraini Suroto; Tyas Utami; Endang Sutriswati Rahayu (Universitas Gadjah Mada, 2023)
The absence of transferable antibiotic resistance genes is required for the safety of commercial probiotics. Previous studies have found that antibiotic resistance genes on plasmids in Lactobacilli make them unsafe for food purposes due to the genes’ ability to transfer to pathogenic microorganisms. In contrast, bacteria from the Lactobacillaceae family are widely used as a probiotic. This study assessed the antibiotic susceptibility of Lactiplantibacillus plantarum subsp. plantarum Kita‐3 (previously known as Lactobacillus plantarum K‐3) isolated from Halloumi cheese using eight antibiotics. Genome sequencing was performed using the Illumina NovaSeq 6000 sequencing platform to detect the presence of antibiotic resistance genes on chromosomes and plasmids. L. plantarum subsp. plantarum Kita‐3 was resistant to clindamycin, streptomycin, and chloramphenicol but susceptible to tetracycline, ampicillin, kanamycin, erythromycin, and ciprofloxacin. Genome sequencing of L. plantarum subsp. plantarum Kita‐3 verified the presence of tetracycline, fluoroquinolones, β‐lactamase resistance genes, and multidrug resistance efflux. Kita‐3 had no transposable elements, gene transfer agents, plasmid‐related functions, or intact prophages. Overall, this study produced the antibiotic resistance profile of L. plantarum subsp. plantarum Kita‐3 to assess the risk of transferring antibiotic resistance genes to other bacteria. The study provides essential data on the safe use of L. plantarum subsp. plantarum Kita‐3 as probiotics.